2022
DOI: 10.1172/jci149473
|View full text |Cite
|
Sign up to set email alerts
|

ATP11B inhibits breast cancer metastasis in a mouse model by suppressing externalization of nonapoptotic phosphatidylserine

Abstract: Cancer metastasis is the cause of the majority of cancer-related deaths. In this study, we demonstrated that no/low expression of ATP11B in conjunction with high expression of PTDSS2, which was negatively regulated by BRCA1, markedly accelerates tumor metastasis. Further analysis revealed that low ATP11Bexpressing and high PTDSS2-expressing (ATP11B low /PTDSS2 high ) cells were associated with poor prognosis and enhanced metastasis in breast cancer patients in general. Mechanistically, an ATP11B low /PTDSS2 hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…RNA pull-down and mass spectrometry were performed to explore potential protein binding partners, and we screened 18 bindings proteins (unique peptide number > 8, PG coverage > 25%) as candidates for LINC00606 to exert tumor regulatory mechanisms in the GBM (Supplementary Table S 7 ). Previous studies have shown that the candidate protein ATP11B is an inhibitor of cancer metastasis [ 40 ] and displays heterogeneous expression in various nerve cell-s in the brain [ 24 ]. ATP11B is closely related to the field of neurology or oncology, so we selected ATP11B as the binding protein for our research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA pull-down and mass spectrometry were performed to explore potential protein binding partners, and we screened 18 bindings proteins (unique peptide number > 8, PG coverage > 25%) as candidates for LINC00606 to exert tumor regulatory mechanisms in the GBM (Supplementary Table S 7 ). Previous studies have shown that the candidate protein ATP11B is an inhibitor of cancer metastasis [ 40 ] and displays heterogeneous expression in various nerve cell-s in the brain [ 24 ]. ATP11B is closely related to the field of neurology or oncology, so we selected ATP11B as the binding protein for our research.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the candidate protein ATP11B is an inhibitor of cancer metastasis [40] and displays heterogeneous expression in various nerve cells in the brain [24]. ATP11B is closely related to the field of neurology or oncology, so we selected ATP11B as the binding protein for our research.…”
Section: Linc00606 Regulates Carcinogenesis By Cooperating With Atp11...mentioning
confidence: 99%
“…Anionic phospholipids, principally PS, are specifically exposed on tumor endothelial cells, possibly in response to oxidative stresses present in the tumor microenvironment [ 22 , 23 ]. Although enhanced PS externalization in cancer is widely accepted, the exact mechanism remains unclear [ 24 ]. Tumor cells and tumor vasculature alter their total phospholipid concentrations, have more PS in the plasma membrane, and have up to sevenfold more externalized PS than healthy cells [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs typically bind directly to proteins to regulate the occurrence and development of disease [30]. Previous studies have shown that ATP11B is an inhibitor of cancer metastasis [31] and displays heterogeneous expression in various nerve cells in the brain [32]. We used the catRAPID website to predict the binding relationship between LINC00606 and ATP11B, uncovering that both these proteins possess RNA binding domains (Supplementary Fig.…”
Section: Linc00606 Regulates Carcinogenesis By Cooperating With Atp11...mentioning
confidence: 99%